Exploring societal solidarity in the context of extreme prematurity - Manya J. Hendriks; Hans Ulrich Bucher; Sabine D. Klein; Jürg C. Streuli; Ruth Baumann-Hölzle; Jean-Claude Fauchère (Swiss Medical Weekly, 2017)
QUESTION